Can Academia be Revolutionary? Barriers to Encourage an Alternative Economics from University Perspective - Manzano-Arrondo, Vicente; Isheloke, Byelongo Elisée (International Journal of Mass Communication, 2024)
There are many publishedcritical works on the hegemonic economics approach. Nevertheless, despite such, its hegemony continues. It does so, in part, and precisely, because of the support it receives from academia. This work questions the reasons for this academic behaviour, and offers the following responses: First, it points to an imbalance between hegemony and its alternatives. The latter is expected to be exhaustive and show sufficient arguments for all its proposals, whereas the first benefits from several cyclic functioning reproduced by inertia. Second, it shows how politics and academia follow two different schools of thought that defend very different conceptions of speed to get results; the exercise of freedom; the management of dissent; ingroup relations; and communications with the public. Third, it reflects on the fact that academia lacks cohesion, is mostly conservative, and is managed by the most obedient and efficient sector of its members. Fourth, it discusses how an academic minority interested in promoting alternatives is tasked with making the operations of hegemony visible to colleagues accustomed to obeying and focused on their compartmentalised work; in return, the minority is often punished by academic norms. Five, it focuses on how academia is absorbed by it through new public management models that marketize academic quality and fill the academic agenda, instead of transforming it. As solutions, the paper suggests the following: (1) creating visible alternatives and building group strength; (2) promoting new quality standards that release the academy from hegemonic conceptions of economics; (3) establishing partnerships with non-academic agents; and (4) transforming how we are teaching economics.